FILSAFAT JIWA IKHWAN AL-SHAFA SEBAGAI BASIS KONSEP PENDIDIKAN - Muhamad Rum (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2021)
This study aims to refute the statement of materialists who tend to reject the existence of the soul as an important dimension for humans, especially those related to education. The background of the problem is that the flow of materialism states that physical reality is the ultimate and this group also rejects the existence of immaterial reality. In relation to physical education, it is the total role in the abstraction process. With education, it is intended to make humans better and able to improve the economy as well. In addition, the education of the bourgeoisie is referred to as a production process, that is, to produce knowledge, human beings that they can use in the life of capitalism. The purpose of this kind of education will reduce the meaning of education as a means to develop human abilities and potentials. Human spiritual potential will be forgotten and not important to be developed to the fullest. The method that the researcher uses in this study is a descriptive and analytical method with reference to the primary and secondary sources of Rasā'il Ikhwān al-Ṣafā related to this research. The conclusion of this study is that education cannot be separated from the immaterial aspect of the soul where all the potential contained in humans comes from the potential of the soul, besides that the soul is also the driving force of the body in carrying out each of its activities. Thus, it is the soul that is the basis of human education, not material-based.